2019
DOI: 10.1111/fwb.13360
|View full text |Cite
|
Sign up to set email alerts
|

Aquatic insects decline in abundance and occupy low‐quality artificial habitats to survive hydrological droughts

Abstract: Hydrological extremes have negative impacts on natural, agricultural, and urban landscapes and place substantial ecological pressure on freshwater habitats. However, the role of artificial freshwater habitats during hydrological drought is poorly understood. Insects make up much of total aquatic fauna and lend themselves to understanding how drought impacts freshwater ecosystems. Using the Greater Cape Floristic Region as an example of a drought‐prone area, we determined the effects of a severe drought on a su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 32 publications
(20 citation statements)
references
References 57 publications
(109 reference statements)
1
19
0
Order By: Relevance
“…The Western Cape province of South Africa, where the current study was conducted, experienced its worst drought in over a century between the years 2015-2017 [53]. Recent analysis of the responses of aquatic biodiversity demonstrated some unusual patterns, with some rare, endemic species that were not found on pre-drought sampling and are now occupying in low quality artificial habitats [54]. Drought could severely impact the community structure of temporary wetlands in the wet phase, as duration of the dry/wet phase changeover within temporary wetlands will influence which species emerge in the wet phase.…”
Section: Plos Onementioning
confidence: 89%
“…The Western Cape province of South Africa, where the current study was conducted, experienced its worst drought in over a century between the years 2015-2017 [53]. Recent analysis of the responses of aquatic biodiversity demonstrated some unusual patterns, with some rare, endemic species that were not found on pre-drought sampling and are now occupying in low quality artificial habitats [54]. Drought could severely impact the community structure of temporary wetlands in the wet phase, as duration of the dry/wet phase changeover within temporary wetlands will influence which species emerge in the wet phase.…”
Section: Plos Onementioning
confidence: 89%
“…The creation of an artificial ditch system that could be used both for irrigation and refuge for the lotic fauna in case of an extreme drought could attenuate the impact of drought on lotic ecosystems 67 . In South Africa, some Cape endemic species occupy artificial reservoirs during severe drought events and use them as refuges until the favorable conditions return in their reproductive areas 68 . This escape behavior is typical of drought-adapted lotic endemics that are dependent on perennial rivers and streams to reproduce and maintain viable populations.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to the general negative role of human disturbance in shaping biodiversity, artificial ponds or tanks associated with agricultural systems have sometimes demonstrated that they are able to sustain biodiversity (Abellán et al, 2006;Declerck et al, 2006;Céréghino et al, 2008;Thiere et al, 2009). These humanmade ponds usually have different environmental characteristics in comparison with natural ponds (e.g., Hill et al, 2016, but see Deacon et al, 2018Deacon et al, , 2019 for similar chemical properties), given that these artificial systems usually have concrete sides and reduced vegetation cover, and possibly higher contaminant inputs compared to natural ponds (Hassall, 2014). Artificial ponds usually show reduced freshwater biodiversity, can support the occurrence of exotic species and may act as possible ecological traps (Oertli and Parris, 2019).…”
Section: Introductionmentioning
confidence: 99%